OPTIMALISASI DESAIN PONDASI MESIN TIPE BLOK PADA PENYELIDIKAN TANAH DI INDRAMAYU (Eternitas: Jurnal Teknik Sipil, 2023)
Along with the development of micro-hydro power plants, machines with very heavy weights are needed, therefore a special foundation is needed that can support the weight of the machine in an active or inactive state. Machine foundations are different from foundations in general, machine foundations require dynamic analysis, namely when the machine is operating, in this study four foundation calculations are taken into account, namely foundations P1, P2, P3 and P4, foundation P1 has dimensions of 10 m long, 3.5 m wide and 2.2 m high, P2 foundation is by widening 2 m, so that the width changes to 5.5 m, as well as for the P3 foundation, namely by extending 2m, so that the dimensions are 12 m long, and for the P4 foundation, by extending and widening 2m, so that the dimensions are 12 m long and 5.5 m wide. The results of the calculation of the static load, the foundations P1 to P4 meet the requirements because the load received by the foundation is 394.66 kN or 39,466 tons, while the carrying capacity exceeds the load, namely 138.13 tons, 217.06 tons, 165.75 tons and 260.7 tons, based on the comparison between the weight of the machine and foundation weight > 3 means that it meets the requirements for the magnitude of the ratio, 4.68, 7.36, 5.62 and 8.83. In addition to static loads, in the planning of machine foundations that need to be checked, namely dynamic loads, namely the value of the ratio of frequency and natural frequencies, the value cannot be less than 1, foundations P1 to P4 have a value of more than 1, which is equal to 1.16, 1.31, 1.22 , and 1.37 for the horizontal direction and 1.14, 1.28, 1.16 and 1.31 for the vertical direction, for the magnification factor value the value must be below 1.5, all foundation models meet the requirements, namely the values ??are 1.44, 1.25, 1.36 and 1.18 for the horizontal direction and 0.88, 0.76, 0.82, and 0.72 for the vertical direction. And what is very important in foundation planning is determining the comfort of workers, foundation P1, is included in Limit Form Machines And, meaning that it is not recommended because it is included in danger to structures, foundations P2, P2 and P3 are included in Trobele some to persons (quite disturbing), foundation P3 is not optimal because the max displacement is only 0.40 inc, type P2 is more effective, namely only by widening the foundation the value drops to 0.38 inc from the previous 0.41 inc on the P1 foundation, while P4 even though the value is 0.38 inc but the dimensions of length and width are larger.
Keywords: Bearing capacity of the Foundation, foundation of the machine